Logical positivism, performativity of images and the neo-baroque – revisiting the myth of totalitarianism - Lacerda-Nobre, Â.; Gameiro, A.; Duarte, R.; Jacquinet, M.; Cunha-Lima, M.; Vega, J.; Graglia, M. (Ata livro de conferência - Social Solidarity Economy & the Commons Conference (4th edition, Lisbon, 13-15 November 2024), 2025)
This text proposes an open reflexion, a work-in-progress exercise that aims at waking up sleeping consciousnesses, in particular the authors’ own existential disquietness. Consequently, the idea is to try to keep as many open knowledge fields as possible as long as they may contribute to understanding the role of communities and of community-led social change as an empowering strategy against totalitarianism. The central message of totalitarianism, in political economy, political science, political philosophy, international economics and international relations (IR) is that it occurs as a self-fuelling mechanism, spreading like wildfire and holding the reigns of myth building, myth construction and myth creation so that the myth is itself the totalitarian phenomenon. Democracy tends to be presented as the antagonist of totalitarianism and it is also based in symbolic production. Two myth building mechanisms are confronted as the clash of Titans, and human history is told according to the narratives that create, feed and sustain the dramaturgy of this open scene. In philosophy, considering epistemic shifts and the history of science, logical positivism emerges in the nineteenth century European white male dominated bourgeois’ context, spreading across the Atlantic leading to pragmatism, and becoming the dominant thinking paradigm across economic science, political science and IR. The myth building process operates through the performativity of images, which consists of the neo-baroque saturation of the rational part of emotions and of the emotional part of rationality. The result is a playing field that reinvents modernity on a daily basis, refusing determinism and reformatting the Enlightenment promise of placing science at the service of human interests: radical and fundamental interests that necessarily are diverse, plural, inclusive, open and are built on trust and empowerment mechanisms. It is literally a new universe of new meanings that imply a deep dive into myth building. That is, from human rights, to fundamental rights, to animal and nature rights, to rights of the original peoples and beyond, a new world of possibilities is emerging. Myths are inescapable yet the power of resignification, i.e., to re-allocate, dislocate, denotate, connotate and detonate differently, is open and infinite.